Adaptive gamification: User/player type and game elements mapping - Ryan Macdonell Andrias; Mohd Shahrizal Sunar; Stephen Laison Sondoh Jr. (Springer, 2022)
Gamification is defined as the use of game design elements in nongame contexts. It is noteworthy that a user preference towards a game mechanic and game element is different as an individual. A common approach to satisfy user expectations is to include multiple game elements to accommodate all the user/player types. However, this approach may cause the user interface to be crowded with irrelevant game elements. This research proposes a method for adaptive gamification design with proper mapping of user/player type and game elements. 915 questionnaires (HEXAD user type) were analysed. Using matrix multiplication/matrix product, we can use correlation analysis to generate two primary relationship output: 1) HEXAD user type with game elements, 2) Six HEXAD user types. The game elements are grouped following Self-determination Theory (SDT); Competence, Relatedness and Autonomy. Rewards are the fourth category, as extrinsic motivation. The fundamental game components that need to be given extra attention during gamification application development are learning, social comparison/pressure, non-linear gameplay and point features. In the meantime, less attention to leaderboard and creativity tools. The adaptive user types and game elements mapping can be used as a clear guideline for the gamification designer to develop an engaging application.